Carbon materials derived from chitosan/cellulose cryogel-supported zeolite imidazole frameworks for potential supercapacitor application. (1st November 2017) - Li, Zehui; Yang, Lan; Cao, Hongbin; Chang, Yu; Tang, Kexin; Cao, Zhiqin; Chang, Junjun; Cao, Youpeng; Wang, Wenbo; Gao, Meng; Liu, Chenming; Liu, Dagang; et al.
Highlights: The strength of cellulose/chitosan cryogels could be improved by adding ZIFs. The structure and pore size of carbon cryogels could be tunable by adding ZIFs. Forming sandwich and bead structure could efficiently improve the capacitance performance of carbon cryogels. Ratios of pyrrolic-N and graphitic-N to total N content were improved after adding ZIF-7. ZIF-7 was better than other ZIFs to enhance the electrochemical performance of carbon cryogel. Abstract: In order to promote sustainable development, green and renewable clean energy technologies continue to be developed to meet the growing demand for energy, such as supercapacitor, fuel cells and lithium-ion battery. It is urgent to develop appropriate nanomaterials for these energy technologies to reduce the volume of the device, improve the efficiency of energy conversion and enlarge the energy storage capacity. Here, chitosan/cellulose carbon cryogel (CCS/CCL) were designed and synthesized. Through the introduction of zeolite imidazole frameworks (ZIFs) into the chitosan/cellulose cryogels, the obtained materials showed a microstructure of ZIF-7 (a kind of ZIFs) coated chitosan/cellulose fibers (CS/CL). After carbonizing, the as-prepared carbonized ZIF-7@cellulose cryogel (NC@CCL, NC is carbonized ZIF-7) and carbonized ZIF-7@chitosan cryogel (NC@CCS) exhibited suitable microspore contents of 34.37% and 30%, respectively, and they both showed an internal resistance lower than 2 Ω. Thereby, NC@CCL and NC@CCS exhibited a high specific capacitance of 150.4 F g −1 and 173.1 F g −1, respectively, which were much higher than those of the original materials. This approach offers a facile method for improving the strength and electronic conductivity of carbon cryogel derived from nature polymers, and also efficiently inhibits the agglomeration of cryogel during carbonization in high temperature, which opens a novel avenue for the development of carbon cryogel materials for application in energy conversion systems.